The Usage Of Magic Box-Based APE as an Effort To Improve Cognitive Aspects - Hambali, Hambali; Harmonis, Mistria; Rozi, Fathor; Milla, Munhidatul (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
This research is to find out The Usage of Magic Box-Based as An Effort in improving cognitive aspects of youth capability identifies and keep in mind animal pictures, fruits, number and alphabet. The method used is a qualitative approach with a sort of case research, meanwhile, based on data and survey that investigator was carried out by observation, inerview and documentation. Investigator formerly attach data obtained through interviews. In this sub-chapter, the result of inetrviews will be explained regarding The Usage of Magic Boxes in Improving Youth’s Cognitive Aspects. The technical data analysis carried out empirically, which begins swith observation and aware of used methods. As the subject of this research is an early childhood, Mawar group RA Walisongo Gayam Sumenep with a total of 20 childern. Result of scope research found that learning process could be implemented with a Learning Approachment Based of Magic Box where there are several steps to implement through creativity in every single youth’s presentation, the active interaction of youth through Magic Box, quiz presentation pass through thuse, provide positive feedback against youth. The implication obtained is the significant of an approachment that teachers employed, by utilizing other play methods that is effective will be competent to stimulate proggress of youth’s cognitive aspects.